2017
DOI: 10.1093/her/cyx039
|View full text |Cite
|
Sign up to set email alerts
|

A comparative effectiveness education trial for lifestyle health behavior change in African Americans

Abstract: Obesity and excess weight are significant clinical and public health issues that disproportionately affect African Americans because of physical inactivity and unhealthy eating. We compared the effects of alternate behavioral interventions on obesity-related health behaviors. We conducted a comparative effectiveness education trial in a community-based sample of 530 adult African Americans. Outcomes variables were physical activity (PA) and fruit and vegetable intake. Outcomes were evaluated at baseline and 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Men who reported no physical activity during the past month, those who reported that they had been physically active during the past month, but had not been active during the past week, and those who reported physical activity, but did not meet the physical activity guidelines (eg, less than 150 minutes/week) were coded as not meeting guidelines. 17 The remaining participants were coded as having met the guidelines for physical activity. 17…”
Section: Methodsmentioning
confidence: 99%
“…Men who reported no physical activity during the past month, those who reported that they had been physically active during the past month, but had not been active during the past week, and those who reported physical activity, but did not meet the physical activity guidelines (eg, less than 150 minutes/week) were coded as not meeting guidelines. 17 The remaining participants were coded as having met the guidelines for physical activity. 17…”
Section: Methodsmentioning
confidence: 99%
“…These items were adapted from our previous research on integrated risk factor education. 15 Specifically, participants were asked how ready they were to start trying to lose weight or keeping their weight the same (1 = not at all/have not thought about it, 2 = a little ready, 3 = somewhat ready, 4 = very ready, 5 = already trying to lose weight/keep weight the same) to measure readiness for weight loss. Responses to this item were re-coded into a dichotomous variable that reflected ready (very ready/already trying to lose or keep weight the same) or not ready (not at all/a little ready/somewhat ready).…”
Section: Methodsmentioning
confidence: 99%
“…During the initial project period, the partnership conducted formative research to understand the needs and preferences of African American residents [ 40 ], translated these data into interventions that targeted these needs and priorities [ 41 ], and evaluated the feasibility and reach of these approaches [ 42 ]. For instance, the Consortium developed two approaches for motivating behavior change in terms of fruit and vegetable intake and physical activity and conducted a comparative effectiveness trial that evaluated the effects of integrated (INT) versus disease-specific (DSE) risk education on changes in dietary behaviors and physical activity in a community sample of African American men and women [ 43 ]. An important goal for the INT intervention was to help participants to see the connection between risk factors for cancer and CVD to motivate health behavior changes.…”
Section: Community Based Participatory Research For Health Behavior Changementioning
confidence: 99%